Corporate Governance and Bank Insolvency Risk : International Evidence - Anginer, Deniz; Demirguc-Kunt, Asli; Huizinga, Harry; Ma, Kebin (World Bank Group, Washington, DC, 2014)
This paper finds that shareholder-friendly corporate governance is positively associated with bank insolvency risk, as proxied by the Z-score and the Merton's distance to default measure, for an international sample of banks over the 2004-08 period. Banks are special in that "good" corporate governance increases bank insolvency risk relatively more for banks that are large and located in countries with sound public finances, as banks aim to exploit the financial safety net. Good corporate governance is specifically associated with higher asset volatility, more nonperforming loans, and a lower tangible capital ratio. Furthermore, good corporate governance is associated with more bank risk-taking at times of rapid economic expansion. Consistent with increased risk-taking, good corporate governance is associated with a higher valuation of the implicit insurance provided by the financial safety net, especially in the case of large banks. These results underline the importance of the financial safety net and too-big-to-fail policies in encouraging excessive risk-taking by banks.